Perceptions of wilderness and the Antarctic: case studies from the United States. Issue 2 (3rd July 2018) - Tin, Tina; O'Reilly, Jessica; Peden, John; Pinkalla, Stephanie; Kelly, Molly; Larrea, Kathy; Haugen, Brynn; Haun, Angela; Janssen, Grace
ABSTRACT: Wilderness is a vital Antarctic symbol. The United States' extensive experience of wilderness protection at home and long-standing engagement in the Antarctic Treaty System make it an ideal candidate to galvanise support in the protection of Antarctica's wilderness values. As a democracy, the nation's policies can be influenced by its people's values. This study aims to contribute to the protection of Antarctica's wilderness values by examining the interrelationships between some Americans' perceptions of wilderness and Antarctica and wilderness management in the US. Using ethnographic interviews and questionnaires, we collected information on perceptions of wilderness in general, and the Antarctic wilderness in particular, from university students and community members in the southern and Midwestern US on three occasions between 2012 and 2013. A total of 462 responses were analysed. Participants had low levels of knowledge about Antarctica. They relied on their cultural understandings of wilderness, which were distinctly American, to conceptualise Antarctica's wilderness values. Many participants expressed a desire to maintain and protect wilderness areas from development, protect animal species and refrain from degradation of the land. The majority of participants stated that the importance of Antarctica lies in it being one of the world's last great wildernesses and an important component of the Earth's climate system. An overwhelming majority supported designating Antarctica as a wilderness reserve where development of infrastructure is limited. Furthermore, study participants' low levels of knowledge about Antarctica and the complex relationships between science, Antarctica and climate change raise questions about forms of governance and human engagement in the Antarctic wilderness that can be truly of interest to humankind.